The women's mosque of America authority and community in US Islam - Ali, Tazeen M. (New York New York University Press, 2022)
"The Women's Mosque of America analyzes how American Muslim women cultivate new forms of Islamic authority that contend with gender inequality, anti-Blackness, and global Islamophobia by approaching the Qur'an as a tool for social justice and community building, providing insights on Islamic authority at the intersections of gender, religious space, and national belonging"--
Includes bibliographical references and index
Keywords: Muslim Women -- United States; Women in Islam; Muslim Women -- Religious life -- United States; Women's Rights -- Religious aspects -- Islam